Inhibitory effects of Scots pine heartwood extractives on enzymatic holocellulose hydrolysis by wood decaying fungi. (August 2018) - Belt, Tiina; Mollerup, Filip; Hänninen, Tuomas; Rautkari, Lauri
Abstract: The heartwood of Scots pine contains extractives that protect it against wood decaying fungi. Pine extractives such as pinosylvins are fungicidal compounds, but they may also have other mechanisms of action. This experiment investigated whether pinosylvins and other heartwood extractives can act as inhibitors of holocellulose hydrolysis, similarly to many other biomass-derived phenolic compounds. The inhibitory properties of extractives were studied against enzymes secreted by a brown rot ( Coniophora puteana ) and a white rot fungus ( Trametes versicolor ), as well as against a commercial Trichoderma reesei enzyme cocktail. The extractives were studied as wood-free extracts and extractives-containing wood powders. In all experiments, the behaviour of the white rot differed from that of the other two. The white rot hydrolases were strongly inhibited and deactivated by extractives, particularly pinosylvins, whereas the others showed only mild or moderate inhibition and no deactivation. The white rot enzymes seemed to modify the pinosylvins, with further studies suggesting that the modified pinosylvins may form complexes with enzymes and cause their deactivation. These results suggest that pine heartwood extractives have potential to contribute to decay resistance as hydrolase inhibitors but only when the fungus produces enzymes capable of modifying the extractives. Graphical abstract: Highlights: Heartwood extractives were tested as hydrolase inhibitors. Extractives showed mild to moderate inhibition of brown rot and Trichoderma enzymes. White rot enzymes were strongly inhibited and deactivated by extractives. Pinosylvins-rich extract was the strongest inhibitor of white rot hydrolases. Enzymes present in the white rot cocktail appeared to modify pinosylvins.